Translation Ideology And Pronoun Equivalence In The Arabic-English Translation Of Surah Al Kahfi - Istimrorul Khair; Moh Gufron; Muh Junaidi (Jurnal Ilmiah Mandala Education (JIME), 2026)
Translation is the process of substituting text in the target language (TL) for text in the source language (SL). Catford 1965 said determining translation equivalency between two distinct linguistic systems is the main challenge intranslating. This research between Arabic-English translation that is actually has a big differents, aim to the distribution and percentage of pronouns containing in Surah Al-Kahfi, and investigates the translation ideology in the Arabic-English translation of Surah Al-Kahfi. The study using a descriptive qualitative method supported by quantitative analysis or Mixed Methode. The data consist of 532 pronouns identified from the Arabic text and its English translation.The pronouns are classified into personal pronouns, possessive pronouns, attached pronouns, and implicit pronouns. The pronouns are classified into shift type, tehniques type, ideology type and equivalence in translation. Shift type divided into unit shift, structural shift and split spit. Tehniques type divided into literal, transposition, amplification, reduction. Translation Ideology divided into foreignization and domestication, and Equivalence divided into formal and dynamic. The Findings release that Attached Pronoun and Implicit Pronoun are the majority found at the type of pronoun because AlQuran especially Surah Al Kahfi has the uniqe character. There are also Unit Shift has and Structural Shift are the most dominant categoriesat translation shift according to Catford 1965. Furthermore, Domestication appears slightlymore Dominant than foreignization due to Lawrence Venuti 1995 about translation ideology. At the end equivalenece shows that dynamic is more dominant than formal according to Eugene Nida1964. It is shown that reflecting the translator’s tendency to adapt Arabic grammatical structures to English linguistic norms while maintaining selected Qur’anic character.